THE TRADING FACTORS, RISK BASED FACTOR AND FIRM CHARACTERISTICS AS DETERMINANTS OF LQ45 FIRM STOCK RETURNS LISTED IN INDONESIA STOCK EXCHANGE - Nandya Sarah Utami; isnurhadi isnurhadi; Umar Hamdan (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2018)
This research aims to analyze whether trading factors, risk based factor and firm characteristics influence LQ45 firm stock returns that are listed in Indonesia Stock Exchange. This research use sample of LQ45 firms in Indonesia Stock Exchange. The data chosen is time series from 2013-2016. The variable used in this research consist of dependent and independent variables. Dependent variable in this research is firm stock returns and the independent variables are trading volume, bid-ask spread, beta, firm size and market to book value (MBV). This research use multiple regression analysis using software SPSS 23 to analyze the relation of independent variables to dependent variable. As the result, out of 5 independent variables there are 4 independent variables that positively and significantly influence firm stock return. They are consist of trading volume, bid-ask spread, beta and market to book value (MBV). Meanwhile firm size doesn’t influence firm stock returns significantly. Keywords : stock return, trading volume, bid-ask spread, beta, firm size, mbv